DEMOCRATIC, ACCOUNTABLE STATES ARE IMPOSSIBLE WITHOUT "BEHAVIORAL" HUMANS. (8th February 2018) - PUTTERMAN, Louis
ABSTRACT: Accountable, democratic government is impossible assuming that the self‐interested, rational individuals of traditional economic theory are the only available citizens and officials. Approaching near realization of such a form of government, as occurred in parts of the world during recent generations, required reconfiguring autocratic states with the aid of the actual human impulses that underlie attraction to norms of fairness, capacities to cooperate, desire for social approval, and anger at norm violators. Increasing our understanding of how accountable government began to approach realization during the past two centuries may aid society in preserving and building on this still‐new political arrangement.